Effects of Collaboration in an Online Environment on ESL Tertiary Students’ Writing and Reflective Thinking - Leong, Irene Yoke Chu (2006)
Based on a descriptive study, the main aim of this study was to observe and examine the effects of collaboration versus non-collaboration on students’ writing and reflective thinking skills in an online learning environment. In order to achieve the purpose of this study, students engaged in both collaborative online writing tasks and non-collaborative online writing tasks were observed. The findings of the study indicate possible pedagogical implications for the planning and teaching of an academic writing program for ESL students in an institution of higher learning. They support the relevance of creating a collaborative learning environment in which the act of reflection is integrated to enhance and stimulate students’ cognitive processes and enable them to improve in their writing skills. The findings also show that how students behave in an online collaborative environment influences the way students think and regulate the various writing processes. The study provides evidence that the collaborative learning environment can be a channel to trigger students’ reflective thinking to help them integrate and link ideas learnt at the surface level and to negotiate meaning using higher order thinking skills. The interactive and reflective discussions generated during online collaboration enhanced and provided opportunities for students to transform learning and as a result, improve their writing skills. The study shows that the combination of these two strategies empowered students to hone the behaviours that support successful collaboration and enhanced students’ metacognitive awareness to adopt a deep approach to learning and writing. In conclusion, the study shows that the implementation of telecollaboration and structured reflection during the teaching and learning of writing among ESL tertiary students can encourage students to share and discuss their thoughts and build ideas. The learning environment, which simulates a real life situation, allows students to get into a relationship with the writing tasks and motivate them to negotiate meaning at a deeper level.